Floating nuclear power plants. (20th November 2007) - Verma, S.S.
Nuclear energy, in comparison with other modes of energy generation such as hydro, thermal and non-conventional sources, has high energy density with little environmental pollution or greenhouse gas emissions. The methodologies to check the problems of nuclear radiation hazards and waste associated with this technology are continuously being developed towards perfection. The nuclear plants are generally built to high safety standards and many lessons have been learned from the past. The latest development of a new concept, i.e., floating nuclear power plants, to make more effective use of nuclear power for peaceful purposes is discussed in this paper, highlighting its method, development status, advantages and limitations.